The New Public Health - Tulchinsky, Theodore H.; Cohen, Matan J.; Varavikova, Elena A. (Cambridge, Massachusetts Academic Press, 2023)
"The New Public Health has established itself as a solid textbook throughout the world. Translated into seven languages, this work distinguishes itself from other public health textbooks, which are either highly locally oriented or, if international, lack the specificity of local issues relevant to students' understanding of applied public health in their own setting. Fully revised, the Fourth Edition of The New Public Health provides a unified approach to public health appropriate for graduate students and advance undergraduate students especially for courses in MPH, community health, preventive medicine, community health education programs, community health nursing programs. It is also a valuable resource for health professionals requiring an overview of public health."
Includes bibliographical references and index.
Keywords: Community health services; Health education; Medicine, Preventive; Public health; Public health -- Study and teaching